Ticlopidine-induced subacute cutaneous lupus erythematosus: A case report and literature review - Yi-Ching Chen; Yu-Hung Wu (Wolters Kluwer Medknow Publications, 2014)
Many drugs have been reported to induce lupus in a minority of patients. Ticlopidine hydrochloride inhibits platelet aggregation and is widely used for the prevention of thrombosis. There have been only a few reports of ticlopidine-induced lupus. Here, we review 13 previously reported cases and describe the case of a 71-year-old man with ticlopidine-induced subacute cutaneous lupus erythematosus. His diagnosis was supported by the appearance of papulosquamous skin lesions on sun-exposed areas and detectable anti-Ro/SS-A antibodies, shortly after drug initiation as well as the gradual resolution of these symptoms after the discontinuation of ticlopidine. Our case highlights that when a patient presents with subacute cutaneous lupus erythematosus-like skin lesions, ticlopidine should be considered as a potential causative agent.